Type 2 Diabetes Mellitus in Rats on a High-Fat Diet with Streptozotocin Induction: Evaluation of the Model / Alexander A. Spasov … [et al.] - Spasov, Alexander A.; Babkov, Denis A.; Prilepskaya, Diana R.; Zakharyashcheva, Olga Yu. (Universiti Teknologi MARA Cawangan Selangor, 2018)
Introduction: Type 2 diabetes mellitus (T2DM) is a complex heterogeneous disease linked with genetic conditions and lifestyle, especially dietary component. Development of the accessible experimental animal model of T2DM is indispensable for elucidation of its pathogenesis and identification of novel antidiabetic agents. Methods: Modeling of experimental T2DM were performed on male Wistar rats aged 9-12 weeks with 2 weeks of dietary manipulation (58% of calories from fats) followed with 35 mg·kg-1 i.p. streptozotocin injection. To evaluate the model, we used intraperitoneal glucose and insulin tolerance test and determined fasting blood concentration of glucose, triglycerides, total cholesterol, and insulin. Additional evaluation of the model was performed by administration of pioglitazone (10 mg/kg-1 p.o.) for 7 days. Student’s t-test was used for single variable comparison between two groups. One-way ANOVA followed by Dunnett post hoc test was used for multiple comparisons versus the control group. Results: T2DM model obtained reproduced key metabolic disorders of the disease, including hyperglycemia (p<0.05), hyperinsulinemia (p<0.05), dyslipidemia (p<0.05) and impaired glucose and insulin tolerance (p<0.05). Administration of pioglitazone significantly improved these metabolic disorders. Thus, we obtained a suitable rat model of T2DM for screening of antidiabetic agents. Conclusion: In comparison of our results with other authors’ data, we have found decreased severity of plasma glucose and basal total cholesterol levels impairment, which highlights the need for careful monitoring of biochemical parameters in high-fat diet and streptozotocin-treated rats.